Re-evaluating the impact of unemployment rate on Health outcomes in Nigeria using an ARDL approach - Eze, Afamefuna Angus; Amedu, Amos Nnaemeka (Journal of Economics Education and Entrepreneurship, 2025)
This study examines the impact of unemployment rate on health outcomes in Nigeria from 1985 to 2022. The study adopts the annual time series data obtained from Central Bank of Nigeria (CBN, 2022) Statistical Bulletin and World Development Indicators (WDI, 2022). This study uses life expectancy and child mortality as the two metrics for health outcomes. The ARDL Bounds Test for co-integration shows there exists long run relationship between the variables. The study employed the ARDL model and results show that unemployment rate has negative and positive impacts on the two metrics respectively in both the short run and long run. While other variables like population growth, total labor force, and government expenditure on health show statistically significant impact on life expectancy in Nigeria. The granger causality test shows that there is a bi-directional causality between unemployment rate and child mortality rate in Nigeria; whereas there is no causality running from unemployment rate to life expectancy rate in Nigeria. The study recommends that to improve life expectancy and reduce child mortality, there should be an investment in primary healthcare, health awareness campaigns, education, sustainable economic growth, social safety nets, population control strategies, and a skilled labor force.